Physical activity, sleep pattern and energy expenditure in double-handed offshore sailing - Galvani, C.; Ardigò, L. P.; Alberti, M.; Daniele, F.; Capelli, C. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of the present study was to quantify total energy expenditure, activity energy expenditure and time spent at three levels of physical activity (low, moderate, high intensity) in four two-person crews during a 500-mile double-handed sailing regatta.